The future: Taking veterinary laparoscopy to the next level. Issue 1 (January 2014) - Fransson, Boel
Practical relevance: Laparoscopic surgery minimizes tissue trauma and speeds recovery, but its uptake into veterinary clinical practice has been slow. Clinical challenges: Laparoscopy is distinctly different from traditional open surgery and a reduced working area and loss of depth perception are among the challenges that the surgeon must get to grips with. Indeed, it is often lack of the necessary skills, rather than the cost of equipment, that presents the greatest obstacle. Audience: This article is aimed at practitioners keen to embrace minimally invasive surgery and advises on how to develop excellence in laparoscopic skills. It makes the case for simulation training and outlines methods that can be instituted in practice at low cost and with comparatively little time expenditure. It also describes technological advances that have already increased the success of veterinary 'keyhole' surgery, as well as those that look promising for the future. Evidence base: Simulation training has been an intense area of research and publication within the past 15 years. This article draws on that evidence base and the experience gained by the author and her research team, which is at the forefront of efforts to develop laparoscopic training for veterinarians.